Exploring the Benefits of Advanced Technologies in Fertilizer, Pesticide, and Water Management for Improved Efficiency and Yield Enhancement - Muraty, Kenithia (Newinera Publisher, 2022)
The advantages of new technology in fertilizer, pesticide, and water management for enhanced productivity and yield improvement in precision agriculture are investigated in this thesis. Research of both a quantitative and qualitative nature was conducted as part of the approach in order to offer a thorough knowledge of the influence that improved technology have had on the practices of precision agriculture. The quantitative findings of the research indicate that the use of modern technological practices leads to a large increase in both productiveness and profitability. The qualitative findings emphasize the positive effects on the environment that would follow from a reduction in the use of pesticides and fertilizers, as well as an increase in the sustainability of agricultural operations. Nevertheless, the research also reveals several challenges to adoption, such as the expense involved and a resistance to changing behaviors that have been done traditionally. Getting rid of these obstacles is going to be essential if we want to realize the full potential of precision agricultural methods. In general, this thesis provides important insights into the potential of advanced technologies in fertilizer, pesticide, and water management to promote sustainable and efficient agricultural practices. Additionally, it identifies key areas for future research in this field, which is extremely helpful.